Sustainable EPM rubber compounds. Issue 12 (12th August 2020) - Polgar, L. M.; Migliore, N.; Picchioni, F.; Van Duin, M.
ABSTRACT: Two important aspects that should be considered when designing new, sustainable rubber products are the bio-based character of the rubber compound ingredients and the recyclability of the vulcanized rubber product. In this work, both are addressed by compounding a thermoreversible cross-linked EPM rubber with pyrolysis carbon black and squalane as sustainable filler and plasticizer, respectively. The resulting rubber product is fully reprocessable in the melt and it displays material properties comparable to those of compounds with conventional additives with high retention of the material properties upon reprocessing. Graphical abstract: